Roles of individual prolyl-4-hydroxylase isoforms in the first 24 hours following transient focal cerebral ischaemia: insights from genetically modified mice - Chen, Ruo-Li; Nagel, Simon (The journal of physiology, 2012)
Key points • Cerebral ischaemia results in the activation of multiple pathways that can independently lead to neuronal death. Agents targeting a number of processes at one time are likely to be translated into stroke therapy. • Hypoxia-inducible factor (HIF) is a transcription complex which responds to changes in oxygen. HIF levels are tightly regulated by a group of prolyl hydroxylases (PHDs). • In this study, we investigated the function of each of the HIF-PHDs in the first 24 hours following transient focal cerebral ischaemia by using mice with each isoform genetically suppressed. • We found that the PHD1−/−, PHD2+/−, PHD3−/− mice had different outcomes after inducing ischaemia. In particular, the PHD2+/− mice had an improved rCBF response post-reperfusion with better behavioural scores. The PHD3−/− mice have worse rCBF but no behavioural change. • The information gained enhances understanding of the biological processes involved and informs strategies for therapeutic targeting of the PHD enzymes. Abstract This study investigated the function of each of the hypoxia inducible factor (HIF) prolyl-4-hydroxylase enzymes (PHD1-3) in the first 24 h following transient focal cerebral ischaemia by using mice with each isoform genetically suppressed. Male, 8- to 12-week old PHD1−/−, PHD2+/− and PHD3−/− mice and their wild-type (WT) littermate were subjected to 45 min of middle cerebral artery occlusion (MCAO). During the experiments, regional cerebral blood flow (rCBF) was recorded by laser Doppler flowmetry. Behaviour was assessed at both 2 h and 24 h after reperfusion with a common neuroscore. Infarct volumes, blood-brain barrier (BBB) disruption, cerebral vascular density, apoptosis, reactive oxygen species (ROS), HIF1α, and glycogen levels were then determined using histological and immunohistochemical techniques. When compared to their WT littermates, PHD2+/− mice had significantly increased cerebral microvascular density and more effective restoration of CBF upon reperfusion. PHD2+/− mice showed significantly better functional outcomes and higher activity rates at both 2 h and 24 h after MCAO, associated with significant fewer apoptotic cells in the penumbra and less BBB disruption; PHD3−/− mice had impaired rCBF upon early reperfusion but comparable functional outcomes; PHD1−/− mice did not show any significant changes following the MCAO. Production of ROS, HIF1α staining and glycogen content in the brain were not different in any comparison. Life-long genetic inhibition of PHD enzymes produces different effects on outcome in the first 24 h after transient cerebral ischaemia. These need to be considered in optimizing therapeutic effects of PHD inhibitors, particularly when isoform specific inhibitors become available.
First published: 24 May 2012
Gesehen am 28.06.2018